Preparation, characterization and antibacterial property of rare earth (Dy and Ce) doping on ZrO2 nanoparticles prepared by co-precipitation method. (2018) - Mekala, R.; Deepa, B.; Rajendran, V.
Abstract: Undoped and rare earth (Dysprosium and Cerium) doped ZrO2 nanoparticles (NPs) were synthesized by Co-precipitation Method (CPM). Urea has used as a precipitator and zirconyl nitrate, dysprosium (III) nitrate pentahydrate, cerium (III) nitrate hexahydrate as starting materials in a pre-heated furnace of around 600°C. The as-synthesized products were characterized by X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive X-ray analysis (EDX) and Ultra-Violet (UVvis-DRS) analysis. XRD study revealed that the synthesized nanoparticles exhibited tetragonal (t- ZrO2 ) and monoclinic (m- ZrO2 ) phase of ZrO2 nanoparticles and also confirm the decrease in the crystallite size with Dy and Ce doping. It was observed that the shape of the nanoparticles is affected by the nature of dopant. EDX study confirmed the presence of Zr, Dy, Ce and O and appropriate increase in the Dy and Ce proportion in the final product. Diffuse reflectance results revealed that the addition of dopant significantly enhanced the optical bandgap value of 2.48, 2.51 and 2.62eV for undoped, Dy and Ce doped ZrO2 nanoparticles, due to basis of oxygen vacancies present within the samples. Furthermore, the undoped, Dy and Ce doped ZrO2 nanoparticles showed no toxicity and possessed a good antibacterial ability against both Bacillus Subtilis (B.subtilis) and Klebsiella Pneumoniae (K.pneumoniae ) cell.